New polyketides and norterpenoids from the marine sponge Diacarnus megaspinorhabdosa. Issue 14 (3rd April 2020) - Miao, Xian-Xian; Chen, Meng-Xuan; Zhu, Hong-Rui; Sun, Fan; Hong, Li-Li; Wu, Wen-Hui; Lin, Hou-Wen; Yang, Fan
Abstract: Two new polyketides (1 –2 ), four new norterpenoids (3 –6 ), together with five known compounds (7 –11 ) were isolated from the marine sponge Diacarnus megaspinorhabdosa . The new structures were determined by extensive spectroscopic analyses, ECD spectra comparison, and Mosher's method. The cytotoxicities towards six cancer cell lines together with the antimicrobial activity against methicillin-resistant Staphylococcus aureus, Canadida albicans, and Escherichia coli were valuated. Compound 10 showed cytotoxicities towards cancer cell lines SW480, NCI–H460, PC−9, and HepG2, with IC50 3.7, 7.8, 6.2 and 8.0 μM respectively. Graphical abstract: Image 1 Highlights: Two new polyketides, four new norterpenoids, along with five known compounds were obtained and identified from the marine sponge Diacarnus megaspinorhabdosa. Compound 10 showed cytotoxicities towards cancer cell lines SW480, NCI–H460, PC-9, and HepG2, with IC50 3.7, 7.8, 6.2 and 8.0 μM, respectively.